MANAJEMEN PELAYANAN PENANGGULANGAN KASUS HIV-AIDS DI KOTA YOGYAKARTA - Gerry Katon Mahendra; Hari Akbar Sugiantoro (The Indonesian Journal of Public Administration (IJPA), 2018)
ABSTRACT : The high number of HIV AIDS cases in the city of Yogyakarta requires the authorities to take appropriate action so that the spread of this virus can be minimized. KPAD has important duties and positions to provide maximum services for vulnerable community groups infected with the virus. based on the results of research, public service management applied in KPA Kota Yogyakarta is more coordinative and indirect service. They focus on maximizing the role of OPDs, NGOs, and communities in order to reach out to vulnerable communities who are infected with the HIV AIDS virus. This measure is effectively marked by the multitude of coordination activities between institutions so as to identify HIV sufferers from the early stages and provide the right follow-up.Keywords : Public Service, National AIDS Commission, HIV AIDS ABSTRAK : Tingginya kasus HIV AIDS di Kota Yogyakarta menuntut pihak berwenang melakukan tindakan yang tepat agar penyebaran virus ini dapat diminimalisir. KPAD memiliki tugas dan posisi penting guna memberikan pelayanan maksimal bagi kelompok masyarakat rentan terinfeksi virus tersebut. berdasarkan hasil penelitian, manajemen pelayanan publik yang diterapkan di KPA Kota Yogyakarta lebih bersifat koordinatif dan pelayanan tidak langsung. Mereka fokus pada memaksimalkan peran OPD, LSM, dan masyarakat guna menjangkau kelompok masyarakat yang rentan terinfeksi virus HIV AIDS. Langkah ini dinilai efektif ditandai dengan banyaknya kegiatan koordinatif antar lembaga sehingga mampu mengidentifikasi penderita HIV dari tahap awal dan memberikan pelayaan lanjutan yang tepat.Kata Kunci : Pelayanan Publik, Komisi Penanggulangan AIDS, HIV AIDS